Design of innovative pedagogical systems as a transdisciplinary-oriented concept - Viktoriia V. Dokuchaieva (Academy of Cognitive and Natural Sciences, 2022)
In a general sense, the concept of research and its strategy are correlated in such a way that the logic of the presentation of the concept should reflect the strategy. In addition, the conceptually proclaimed technology of designing innovative pedagogical systems acts, in relation to the research strategy, as the tactics of the researching subject. If we take into account that the research is carried out on an interdisciplinary basis, then the design strategy produced on the basis of an interdisciplinary synthesis, at each of its stages, is expected (guaranteed) to lead to new interdisciplinary achievements - theoretical constructs (knowledge), models, algorithms, technologies, etc.: they serve as a reliable gnostic tool in further research carried out outside a specific disciplinary context. In other words, the results of interdisciplinary synthesis turn into a transdisciplinary strategic research tool, which we tried to demonstrate in this article.